Coco de roda novo quilombo: saberes da cultura popular e práticas de educação popular na comunidade quilombola de Ipiranga no Conde-PB - Silva, Cicero Pedroza da (2014)
This study, entitled "COCO DE RODE NEW QUILOMBO: knowledge and practices of Popular Culture Popular Education in maroon community of Ipiranga in Conde -PB", is mainly aimed to analyze the historical, cultural, social and political contribution of the maroon community of Ipiranga in Conde-PB for the construction of educational practices in Freire's perspective of Popular Education. Located, methodologically, the precepts of qualitative research approach, while action research, investigates a maroon territory many struggles and social facts relevant to the history of Paraíba, specifically in the South coast Gramame valley. For its realization, we engage as participants in educational activities with the Collective Aquatune and the Association of Residents of Ipiranga, considering that the subject of our research are the Coco de Roda New Quilombo members. Used as tools for data collection: semi-structured interview following the use of recorder; form to identify a profile of respondents in the group; field diary, photo coverage and participant observation. And for data analysis used the technique of content analysis. We seek to develop a critical analysis of systematic observation of maroon territory locus of our research, considering the population growth of communities to better interpret the reality of those involved in this research, especially with regard to the connection between the existing knowledge Popular Culture and practices Popular Education quilombo of Ipiranga in Conde-PB. Overall the results revealed a process of awareness within the Coco de Roda New Quilombo group, confirming the raised earlier this investigation, the relationships with the subjects, the intention of educating the teaching-learning process of knowledge transfer hypothesis of over old to the young and with the planning, dialogues, deliberations and organizations who value the ideas and popular culture, while expression of popular knowledge. Hence the importance of this group in the lives of the subjects of action research. Overall, we believe that the Coco de Roda New Quilombo has contributed to the Popular Culture and Popular Education of community members, it not only means an expression of Brazilian popular culture (cultural heritage), as well as a historical control strategy therefore, if in the past was used to camouflage the meetings and political articulations that gave beginning to plan fights and escapes to the quilombo nowadays is used as a struggle and mobilization for land reform strategy, the identity of the maroon people, finally by the appreciation of popular culture. In addition to being based on values such as respect for elders and youngsters, justice and social equality.